Information Visualisation, Gamification and Immersive Technologies in Participatory Planning - Christodoulou, Nektarios; Papallas, Andreas; Kostic, Zona; Nacke, Lennart E. (My University, 2018)
Public participation in the decision-making processes that shape the urban environments we inhabit is an imperative aspect of a democratic society. Recent developments in the fields of Information Visualization, Gamification and Immersive Technologies (AR/VR/MR) offer novel opportunities for civic engagement in the planning process that remain largely unexplored. This SIG aims to identify ways in which these technologies can be used to tackle the public participation challenges identified by the European Commission, the UN Habitat and the World Bank and experienced by citizens across the world. The overarching goal of this SIG is to define methods and processes where technology can facilitate public participation in the planning process for the inclusive and democratic development of our cities. The overarching goal of this SIG is to bring together an interdisciplinary group of practitioners, academics and policy makers from the CHI communities (Design, User Experience, HCI for Development (HCI4D), Sustainability and Games & Entertainment) and beyond, to discuss innovative ways to increase the transparency, accountability and democratic legitimacy of this innately political process.
Keywords: Augmented reality; Gamification; Immersive technologies; Information visualization; Participatory planning; Public participation; Urban planning